The role of interannual rainfall variability on runoff generation in a small dry sub-humid watershed with disperse tree cover - Schnabel, S; Gomez GUTIÉRREZ, A (Cuadernos de Investigación Geográfica, 2013)
Recent studies in small experimental catchments under Mediterranean-type climate revealed a complex hydrological catchment response, presenting saturation excess runoff generation and, to a minor degree, infiltration excess flow. Many of these catchments, however, belong to areas with sub-humid or humid Mediterranean climate. Catchment studies were carried out since 1991 in savannah-like grazed land (dehesas), which are widespread in south-western Spain, and also elsewhere in the Mediterranean. Albeit knowledge gained by previous studies, no thorough analysis has been carried out on the temporal variation of discharge production using the complete dataset. The objectives include i) an analysis of the temporal variation of discharge and rainfall at different temporal scales, ii) exploration of the role of antecedent soil moisture conditions in runoff production, iii) empirical modeling of rainfall- runoff relationships at the event scale and iv) definition of the importance of interannual rainfall variation on discharge production. The analysis were based on rainfall and runoff which were monitored at a time resolution of 5 minutes and periodically measured soil moisture from various depth in the valley bottom. Regression analysis as well as the comparison of hydrographs illustrate on the importance of antecedent rainfall conditions. Soil moisture in the valley bottom was crucial to understand the hydrological behaviour of the catchment. A soil moisture threshold of 0.37 m3 m-3 was defined above which runoff coefficients increase sharply. This situation is reached with 170 mm of antecedent rain falling in a continuous way. The results indicate that saturation excess flow and preferential subsurface flow processes are responsible of most of the runoff generated. Hortonian type overland flow dominates under dry soil conditions and is produced by high intensity rainfall. Non-linear regression analysis with data grouped according to antecedent catchment conditions produced highly significant regression models, explaining event discharge with three variables: Maximum 60-minute rainfall intensity (I60), event rainfall minus I60 and mean antecedent daily rainfall. Variability of monthly runoff is best explained by interannual rainfall variation rather than by mean seasonal distribution. During droughts, which are a common feature in the Mediterranean, discharge was very low. Runoff is highly concentrated in time with 10% of the months accounting for 85% of total discharge.
Keywords: Dehesa; discharge; Drought; empirical modelling; RAINFALL; Soil moisture